Enteric coating of hard gelatin capsules by the spouted bed process - H.V.A. Oliveira, M.P.G. Peixoto, L.A. Tacon & L.A.P.Freitas (Journal of Applied Pharmaceutical Science, 2013)
The aim of this work was to study the aqueous enteric film coating of hard gelatin capsules in a single step, with no sub coats. A lab scale spouted bed coater with bottom spray feed was employed to coat capsules using gastric resistant methacrylic polymer Eudragit® L30D55. Preliminary experiments were carried out to determine an appropriate coating suspension formulation and to characterize the fluidization behavior of the capsules. Process factor effects, such as the coating time, coating solution viscosity and substrate load on capsule weight gain were studied using a full factorial 23 design. Coating efficiencies ranged from 69.5 to 84.9% and weight gain from 10.8 to 33.2%. The suspension viscosity did not affect significantly the efficiencies. The percentages of gastric resistant capsules increased linearly with weight gains. 100% of the capsules were shown to be gastric-resistant when coated with a minimum of 17% mass increase and their dissolution profiles showed less than 5% drug release after 2 h in HCl solution.
Keywords: Eudragit® L30 D55, weight gain, sodium diclofena